Pathologically Complete Response after Triple Therapy in Locally Advanced Esophageal Cancer in a Hereditary Hemorrhagic Telangiectasia Patient - Robin Park (Case Reports in Oncology, 2020)
Hereditary hemorrhagic telangiectasia (HHT) is a disorder characterized by vascular manifestations including mucocutaneous and visceral telangiectasias and arteriovenous malformations. Herein we present the case of a relatively young patient with HHT with an incidentally discovered locally advanced esophageal cancer on endoscopic screening and pathologically complete response after neoadjuvant chemoradiation. This case highlights an unusual tumor response to chemoradiation in locally advanced esophageal cancer, and the surveillance care of HHT patients.